UPAYA GURU DALAM PEMBENTUKAN AKHLAK SISWA MELALUI KEGIATAN EKSTRAKULIKULER BACA TULIS AL-QUR’AN DI MA NEGERI KOTA BATU - Ibrahim Maulana Syahid Nur A’la1; Muhammad Hanief; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The behavior change in MAN Batu Malang City students needs to be anticipated with a strong religious foundation, one of which is through the form of al-Qur'an literary extracurricular activities in MA Negeri Kota Batu. This behavior change is influenced by this city is the center of a tourist city in East Java and the rapid development of technology 4.0. this Extracurricular is wrong way of anticipating it, wearing the Qur'an is the core of the teachings of Islam which contains noble morality.The research approach is qualitative and the type of case study research is described descriptively. Data collection techniques using observation, in-depth interviews and documentation. While the analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data refers to the credibility criteria (degree of trust), which starts with the depth of observation, data triangulation and member checks. The findings in this research extracurricular activities are able to maintain and change the morals of students in a positive direction by inserting a moral message in each process of teaching and learning to read and write the Qur'an, and tries to exemplify the morality of the mercy through the behavior he applied to this activity.